Rationale for selecting antihistamine drugs for the therapy of chronic urticaria in terms of efficacy and safety - O. V. Skorokhodkina; S. V. Klyucharyova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Goal of the study. To compare the efficacy of antihistamine drugs for the therapy of chronic urticaria taking into consideration their effect on the patients' cognitive functions. Materials and methods. The study involved 178 patients with chronic urticaria who were divided into six groups taking second generation antihistamine drugs: Cetirizine (n = 38), Levocetirizine (n = 27), Fexofenadine (n=26), Ebastine (n = 33), Loratadine (n = 26) and Desloratadine (n = 28). The patients recorded dynamic changes in clinical symptoms of the disease (number of urticarial components, skin itching intensity, availability or absence of urticarial derniographism, angioedema signs and signs of the shortness of breath and reduced blood pressure) in their individual diaries. Baseline signs of the patients' cognitive condition and those recorded during the treatment were studied using the Kraepelin's arithmetic test (modified by Schulte), I.M. Lushchikhina's verbal and visual thinking assessment method and method for memorizing ten words. The control group comprised 31 subjects without chronic urticaria. Results of the study. Ebastine and Fexofenadine are the most efficient antihistamine drugs for the treatment of chronic urticaria. At the same time, they do not have any negative effect on the patients' cognitive functions so they can be recommended for long-term treatment of chronic urticaria. In spite of its evident positive therapeutic effect, Cetirizine reduces mental alertness and deteriorates thinking in patients with chronic urticaria. Because of this, the drug must be prescribed with care for long-term administration to those patients whose professional activities demand increased attention concentration. Loratadine has a positive effect on the patients' attention and thinking. However, taking into consideration its low efficacy, the drug can be prescribed as the basis therapy for the treatment of light forms of chronic urticaria.